2021
DOI: 10.1111/cas.15158
|View full text |Cite
|
Sign up to set email alerts
|

HLA genotyping in Japanese patients with multiple myeloma receiving bortezomib: An exploratory biomarker study of JCOG1105 (JCOG1105A1)

Abstract: Bortezomib (Btz) shows robust efficacy in patients with multiple myeloma (MM); however, some patients experience suboptimal responses and show specific toxicities. Therefore, we attempted to identify specific HLA alleles associated with Btz‐related toxicities and response to treatment. Eighty‐two transplant‐ineligible patients with newly diagnosed MM enrolled in a phase II study (JCOG1105) comparing two less intensive melphalan, prednisolone, plus Btz (MPB) regimens were subjected to HLA typing. The frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…CD8+ T cell dependent killing of cancer cells requires appropriate presentation of tumor antigens by MHC, which in humans is human leukocyte antigen (HLA) molecules, resulting in at least three kinds of biomarkers: specific HLA genotype for certain cancer type ( 115 ), some kind of HLA alleles having strong antigen presentation ability ( 116 ), and high HLA diversity which could provide a large library and are more likely to have appropriate HLA ( 117 ). An exploratory study of multiple myeloma patients treated with bortezomib found some HLA alleles as candidates, as patients carrying HLA-DQB1*03:02, HLA-DQB1*05:01, and HLA-DRB1*01:01 class II alleles are more likely to get a complete response ( 115 ). In 1535 advanced cancer patients treated with ICIs, the HLA-B44 supertype is associated with extended survival, whereas the HLA-B62 supertype was associated with poor outcomes ( 116 ).…”
Section: Biomarkers: Direct Predictive Factors In Idmentioning
confidence: 99%
“…CD8+ T cell dependent killing of cancer cells requires appropriate presentation of tumor antigens by MHC, which in humans is human leukocyte antigen (HLA) molecules, resulting in at least three kinds of biomarkers: specific HLA genotype for certain cancer type ( 115 ), some kind of HLA alleles having strong antigen presentation ability ( 116 ), and high HLA diversity which could provide a large library and are more likely to have appropriate HLA ( 117 ). An exploratory study of multiple myeloma patients treated with bortezomib found some HLA alleles as candidates, as patients carrying HLA-DQB1*03:02, HLA-DQB1*05:01, and HLA-DRB1*01:01 class II alleles are more likely to get a complete response ( 115 ). In 1535 advanced cancer patients treated with ICIs, the HLA-B44 supertype is associated with extended survival, whereas the HLA-B62 supertype was associated with poor outcomes ( 116 ).…”
Section: Biomarkers: Direct Predictive Factors In Idmentioning
confidence: 99%